Experiences of family caregivers regarding a community‐based care‐ and case‐management intervention. A qualitative study. (12th May 2021) - Warkentin, Nicole; Wilfling, Denise; Laag, Sonja; Goetz, Katja
Abstract: Family caregivers play an essential role in healthcare for elderly people in primary care settings. The complexity of geriatric patients as well as the fragmentation of healthcare systems can lead to a burden for family caregivers, which can affect their physical and psychological health as well as social relationships, economic productivity and quality of caregiving. Care‐ and case‐management offers a possibility to support, empower and navigate family caregivers through healthcare systems in order to reduce their own burden. The project RubiN (Continuous care in a regional network) was developed to provide regional care‐ and case‐management for outpatient care of the elderly (age >70 years) in a primary care setting in Germany. The aim of this qualitative study was to explore experiences and attitudes of family caregivers of geriatric patients regarding the community‐based care‐ and case‐management intervention RubiN. Telephone interviews with a purposeful sample of 21 family caregivers enlisted in all RubiN networks were conducted between March and May 2020 and were followed by qualitative content analysis. The main categories, which emerged were namely: (1) current healthcare situation and (2) experiences with RubiN. Main findings suggest that participants in this study valued the provided support and experienced a sense of relief. However, some participants were disappointed with RubiN and the included support by care‐ and case‐managers. A care‐ and case‐management affected caregiving per se as well as the patient's and family caregiver's well‐being. Important aspects contributing to these findings were a continuous relationship, training and expertise of the care‐ and case‐managers. Establishing networks between the patients, family caregivers, care‐ and case‐managers and healthcare providers were key components as well as a good explanation about RubiN itself for family caregivers. Therefore, a community‐based care‐ and case‐management can play an important role in detecting, facilitating and preventing family caregiver burden.